The establishment of baseline data on the rates and processes of soft-tissue decomposition in two terrestrial habitats of the Western Cape, South Africa - Finaughty, Devin Alexander (Department of Human Biology, 2019)
Estimation of the post-mortem interval is an oft-sought outcome of forensic death investigations. This requires knowledge of the local environment and how it affects soft-tissue decomposition. Such knowledge is usually informed by locally-obtained data regarding decomposition. However, no such data exist for the Western Cape, South Africa. The proposed study therefore principally sought to establish baseline data on the rates and processes of soft-tissue decomposition in the Western Cape. Two habitats, representing open and heavily shaded (~covered) conditions and characteristic of those from which forensic cases are derived in the Western Cape’s largest city, Cape Town, were chosen for investigation. Sixteen porcine carcasses serving as analogues for adult human bodies were deployed in these habitats during two summers and two winters between 2014 and 2016. Progression of decomposition was tracked by recording weight loss over time and scoring the carcasses using Megyesi et al.’s (2005) Total Body Score system. Simultaneously, data were gathered on the physical and biotic agents of decay, including prevailing weather conditions and necrophagic faunal activity. These measures were assessed for differences when comparing habitats and seasons, and possible correlations between them were investigated. Carcasses decomposed almost twice as fast in summer compared to winter, but no significant difference was found between habitats within-season. Summer decomposition was marked by precocious natural mummification via desiccation – the first records of this preservative process in intact remains in any temperate climate globally. The first successional patterns for necrophagic insects in the Western Cape were established. The presence of the blow fly Calliphora vicina on decomposing remains represent the first records of this species in the Western Cape since 1976, and confirms its local forensic significance. An unexpected finding was extensive scavenging by Cape grey mongoose (Galeralla pulverulenta), predominantly in the covered habitat, heretofore unreported. These observations, amongst others, confirm the biogeographic uniqueness of decomposition in the Western Cape. This emphasises the importance of furthering our understanding of the local decomposition ecosystem, chief amongst these confirming the taphonomic processes driving precocious natural mummification and determining the taphonomic influence of scavenging in Cape Town.